(untitled) (Research, Society and Development, 2022)
Objective: To identify the determinants and conditions in health related to chronic non-communicable diseases (CNCDs). Materials and methods: This is an integrative literature review (ILR) qualitative approach. In order to develop the guiding question of this ILR, the domains of the PICO strategy were applied, resulting in the question: “What are the diseases related to non-communicable chronic diseases?” A bibliographic survey was carried out in September 2022 in the following databases: LILACS via VHL, and MEDLINE via PubMed. The search strategies were formulated from the mentioned descriptors in Portuguese, English and Spanish, linked by the Boolean operator “AND”. Results: The surveillance of risk and protective factors for CNCDs allows the identification of social, economic and environmental conditions, and the analysis of data by capital can support the planning of programs and local actions for the prevention of chronic diseases and their risk factors, both individual and collective. Conclusion: It is possible to conclude that the prevention and control of CNCDs and their conditions are fundamental to contain the epidemic growth of these diseases and their consequences for the population and the health system.